Excellence and premiership in academia:An interview with Director of CHEPA, Professor William G. Tierney. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
Earlier in the year Professor William G. Tierney from the University of Southern California (USC) had three months academic sojourn at IPPTN.The Institute welcomed him for a much needed contribution in an on-going research. Prof. Tierney was en-route to Australia for the next leg of his sabbatical. Bulletin caught up and chat him up before he left.